Remembrance, Retrospection, and the Women’s Land Army in World War I Britain - White, Bonnie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2011)
This paper explores the methodological challenges posed by interviews with former members of the Women’s Land Army held in Britain’s Imperial War Museum. These interviews were conducted approximately 60 years after the First World War as part of the Women’s War Work Collection that was created in an effort to capture the role of women in the wars of the twentieth century. These documents are certainly of value to the historian, although the decades that passed between event and recollection highlight the problematic relationship between history and memory. The author argues that due to this temporal gap and the continuation of lived experience that shaped both identity and memory in the intervening years, the interviews lose their evidentiary primacy and must be approached as secondary sources, albeit ones grounded in personal experience. This challenge is exacerbated by problems with the interview process itself that guided how the Land Girls’ narratives were reconstructed by the interviewees. This paper works toward a re-evaluation of the usefulness of these oral interviews.